Fire Detection System Using Android-Based Microcontroller - Akbar Rafni Rafsan Jani; Dwipa Handayani; Achmad Noeman (LPPM Universitas Islam 45 Bekasi, 2021)
The Fire Detection System can be supported by Internet of Things technology, e.g. a Microcontroller device which is used to control the related devices. In this study, android-Based fire detection system was designed in which the house owner can always monitor the condition of the house all the times and accessing the information about their house when a fire occurs until the fire suppression process is complete. Information of the house condition will be displayed on the Blynk application which is located in the kitchen area and is connected to several supporting sensors. The design of a Fire Detection System Using an Android-Based Microcontroller is divided into several stages, namely: (1) Requirement Identification; (2) Requirement Analysis;(3) Hardware Design; (4) The software design (Arduino IDE 1.8.5 and Blynk). The testing results showed that the android-based Fire Detection System Using Microcontroller was able to provide information to residents of the house in the real-time.